Pengaruh Stigma Teman Sebaya Terhadap Hubungan Interpersonal - Junevalim Telaumbanua; Elizama Zebua; Hosianna Rodearni Damanik; Famahato Lase (Departement of Mathematics Education, 2024)
Interpersonal relationship skills can be improved by efforts to eradicate the problem of peer stigma. The aim of this research is to reveal the influence of alleviating peer stigma problems (variable X) on interpersonal relationships (variable Y) using quantitative associative strategy methods. The research location was UPTD SMP Negeri 1 Gunungsitoli, the research population was all 320 class VIII students and the sample was drawn by purposive sampling of 32 people. The data collection instrument was a closed questionnaire which was distributed to a number of respondents. Data were analyzed using linear regression analysis to answer research questions according to the proposed hypothesis. The results of the study concluded that there is a significant influence of peer stigma (X) on interpersonal relationships (Y), namely that the more the problem of peer stigma is resolved, the more students' interpersonal relationship abilities will improve. The contribution or contribution of variable X to Y is 96.1%, while the remaining 3.1% is influenced by other variables that have not been studied, and this influence is categorized as very large. The regression coefficient value for variable It is recommended that guidance and counseling teachers plan and implement group guidance services for students with appropriate and appropriate material to alleviate the problem of peer stigma and improve students' interpersonal relationships. Students are also advised to follow it well. Keywords: Stigma, interpersonal relationships